From lockdown to rāhui and teddy bears in windows: Initial responses to Covid‐19 in Aotearoa/New Zealand. Issue 5 (1st October 2020) - TRNKA, SUSANNA
Abstract : Scholarly examinations of states of emergency frequently underscore how the crisis imaginary is employed to rapidly and unjustifiably expand state power. This line of analysis affords great insight into the misuse of state power. It also, however, tends to depict the citizenry as either weak and overwhelmed or at best, duped by the workings of the state, and thus ignores the possibility of democratic processes continuing within a state of emergency. Aotearoa/New Zealand's response to Covid‐19 reveals a collaborative dynamic in which the citizenry actively engaged in constituting the state of emergency, and suggests the need for a broader examination of how collective responsibility, care and blame are envisioned and enacted, not only by governments but by (neo‐liberal) citizenries during times of national crisis.